Antipsychotic prescribing practices and their association with rehospitalization in a forensic psychiatric sample - Goody, Joseph; Petersen, Karen; Brink, Johann; Crocker, Anne G.; Nicholls, Tonia (Frontiers in Psychiatry, 2024)
While there is extensive literature examining the effectiveness of antipsychotic prescribing to patients with schizophrenia spectrum or other psychotic disorders in general psychiatric services, there is a dearth of studies examining antipsychotic prescribing practices and their effectiveness in forensic psychiatric services. Forensic psychiatric patients have unique challenges often due to their high-profile offences, public scrutiny, and legal requirements. This longitudinal, retrospective study aimed to examine antipsychotic prescribing and rehospitalization rates in a forensic psychiatric sample, along with relevant socio-demographic, clinical, and forensic characteristics. All patients had a psychotic illness and were prescribed antipsychotic medication. The sample included 153 patients, of which the majority were male (85.6%), Caucasian (71.2%), middle aged (30s to 50s), had schizophrenia or schizoaffective disorder (76.5%), had a substance use disorder (62.1%), and had a most serious index offence against the person (80.4%). Atypical antipsychotics accounted for the majority of antipsychotic prescriptions (75.9%) and the sample had an antipsychotic polypharmacy rate of 39.9%. The sample was divided into four primary antipsychotic formulation types, which were oral (34.0%), injection (39.2%), clozapine (19.0%), and subtherapeutic (7.8%). Regarding rehospitalization, 52.9% of the sample was rehospitalized, with the average number of rehospitalizations being 1.2 (SD = 1.7) and proportion of the follow up period rehospitalized being 16.4% (SD = 27.7%). Patients prescribed clozapine had numerically lower rates of rehospitalization than those prescibedprescribed oral and injection formulation types, but it was not statistically significant. With a 19.0% prescription rate, clozapine may be underutilized in this sample. Further research is needed to demonstrate the potential benefits of clozapine regarding rehospitalization in forensic psychiatric patients, as has already been done in general psychiatry. Advancing treatment of the high-profile forensic population can reduce stigma toward people with mental illness and criminal justice involvement.